Model for Tourism Clusterisation of Dalmatia as the Umbrella Brand - Krajnović, Aleksandra; Bosna, Jurica; Jašić, Dražen (Oeconomica Jadertina, 2017)
Comprehensive strategic and marketing plan in tourism is necessary to define certain attractive features and products within the tourism umbrella brand and its constituent units - tourism clusters, in order to make them recognisable on the market. Since natural scenic spots are not the only determining factor when choosing a destination anymore, it is necessary to perform a comprehensive branding of other tourist attractions too. This paper presents a model for tourist clusterisation of Dalmatia as the umbrella brand of the region. A portfolio of tourism products and appropriate target markets are defined for each cluster. The paper gives an example of Istria region which defined its tourism clusters by designing the master plan for tourism development for the period 2002-2012. The authors have used the Istria example as the basis for their model for clustering Dalmatia as the regional umbrella brand of tourism. The authors also indicate the characteristics of the model and the opportunities and obstacles to its implementation.
Keywords: umbrella brand in tourism; tourism clusters; tourism regions; tourism product destinations; Dalmatia as a tourism umbrella brand